2014
DOI: 10.1093/hmg/ddu114
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of gene expression in human retina and supporting tissues

Abstract: Understanding the influence of gene expression on the molecular mechanisms underpinning human phenotypic diversity is fundamental to being able to predict health outcomes and treat disease. We have carried out whole transcriptome expression analysis on a series of eight normal human postmortem eyes by RNA sequencing. Here we present data showing that ∼80% of the transcriptome is expressed in the posterior layers of the eye and that there is significant differential expression not only between the layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
110
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(122 citation statements)
references
References 59 publications
11
110
0
Order By: Relevance
“…Different types and functions of the cells in the NR/RPE complex make understanding the overall cholesterol maintenance in the retina diffi cult. Nevertheless, progress has been made, and now we know that the retina obtains cholesterol via local biosynthesis and uptake of blood-borne cholesterol and contains all the genes necessary for independent cholesterol homeostasis (7)(8)(9)(10)(11)(12). The means of cholesterol elimination have also been ascertained and comprise lipoproteinmediated transport to the systemic circulation, metabolism to oxysterols by CYP27A1 and CYP46A1, and PR phagocytosis by the RPE, the retina-specifi c mechanism ( 13,14 ).…”
Section: Cyp27a1mentioning
confidence: 99%
“…Different types and functions of the cells in the NR/RPE complex make understanding the overall cholesterol maintenance in the retina diffi cult. Nevertheless, progress has been made, and now we know that the retina obtains cholesterol via local biosynthesis and uptake of blood-borne cholesterol and contains all the genes necessary for independent cholesterol homeostasis (7)(8)(9)(10)(11)(12). The means of cholesterol elimination have also been ascertained and comprise lipoproteinmediated transport to the systemic circulation, metabolism to oxysterols by CYP27A1 and CYP46A1, and PR phagocytosis by the RPE, the retina-specifi c mechanism ( 13,14 ).…”
Section: Cyp27a1mentioning
confidence: 99%
“…27 Moreover, recent reports have demonstrated that both genes are expressed in the choroid. 28,29 Although the precise mechanisms are unknown, choroidal thickness might be controlled through inflammatory reactions that involve complement activation.…”
Section: Factors Associated With Sct and Cvh In Pcv Yoneyama Et Almentioning
confidence: 99%
“…To maximize their expression data, Li et al (2014) integrated genetic variation data with expression data generated via RNA-seq. Specifically, they generated genotypes using a SNP chip on peripheral blood from each human eye donor to examine whether or not the previously identified SNPs also associated with ophthalmic diseases (including AMD), and showed allele-specific expression (ASE) in their RNA-seq data.…”
Section: Genetic Variationmentioning
confidence: 99%
“…Compared with traditional gene expression microarrays, RNA-seq also has a lower frequency of false-positive findings and a higher reproducibility as measured by validation because of less technical variation (Twine et al 2011;Yendrek et al 2012;Potok et al 2013). To date, only two studies have used RNA-seq to study eye tissue (Farkas et al 2013;Li et al 2014). Specifically, Farkas et al (2013) examined retinal tissue from three donors in their 40s with normal phenotype as defined by no known ocular history.…”
Section: Gene Expression Microarray and Rna-seq Studiesmentioning
confidence: 99%
See 1 more Smart Citation